The Influence of Search Engine Marketing on the Consumer Decision Making Process in South Africa - De Abreu, Delia Maria Freitas (My University, 2014)
Information overload is an issue which consumers are increasingly faced with, and Internet search engines act as a means to assist consumers in overcoming this problem. In an age of technological advancement where Internet and search engine usage has demonstrated exponential growth, marketers have witnessed the emergence of search engine marketing as a new marketing channel of importance. Search engine marketing is unique in that it occurs closer to consumer purchase decisions than any other marketing channel has accomplished before: at the exact moment when a consumer is actually looking for a desired product or service. This research investigates how Internet search engines as marketing channels influence information search, evaluation of alternatives and the purchase decision of South African consumers. A mixed method approach was used as the research paradigm, with a combination of qualitative and quantitative methods. The qualitative phase involved a convenience sample of 10 face-to-face interviews, and the resultant data was content analysed to understand the important issues related to search engine marketing that influence consumer decision processes. These issues were used to develop the questionnaire for the quantitative phase, which was administered electronically and completed by 201 respondents. The resultant data was analysed using exploratory factor analysis. The quantitative study served to confirm the findings from the qualitative study and provide more reliable insights about the population, while ultimately also answering the research questions. The results of this research found that South African consumers’ search for information is influenced by a “search criteria” factor, while the evaluation of alternatives is influenced by an “evaluation criteria” factor, and the purchase decision is influenced by a “purchase criteria” factor, all related to search engine marketing. Additionally, a number of contingency factors, which do not form part of but influence the decision making process of South African consumers, were iii identified as “high and low involvement”, “sponsored listings”, “purchasing offline” and “type of product”. The key message of this research is that search engine marketing campaigns are critical to the long-term profitability of companies operating in an electronic age. The identified factors relating to search engine marketing that influence the decision making process should be considered by marketing managers, and search engine marketing strategies formulated accordingly. And finally, new search engine marketing strategies should ideally be integrated with current marketing strategies to ensure optimal success.
MBA thesis
Keywords: Internet marketing; Consumer behaviour